Professional practice of nurses and influences on moral sensitivity - Danielle de Araújo Moreira; Cecília Maria Lima Cardoso Ferraz; Iluska Pinto da Costa; Jéssica Martins Amaral; Thaís Teixeira Lima; Maria José Menezes Brito (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To understand the professional practice of nurses and their influence on the development of moral sensibility. Methods: A qualitative and descriptive study, conducted between November 2015 and February 2016 in the hospitalization units of the medical clinic of two large hospitals located in Belo Horizonte, Minas Gerais. 14 nurses participated. Data collection was done through interviews, guided by semi-structured scripts. The data were submitted to content analysis. Results: Two categories emerged: Professional practice of the nurse: internal and external goods and Moral sensitivity and the interface with the professional practice of nurses. The development of the moral sensitivity of nurses is influenced by factors related to professional practice, such as interpersonal relations, ethical education and management activities. Final considerations: In the professional practice, moral sensibility is an integral part of the ethical decision-making process in services, being essential for quality care.